2022
DOI: 10.3390/su142114091
|View full text |Cite
|
Sign up to set email alerts
|

Red Deer in Lithuania: History, Status and Management

Abstract: The history, current population status and (un)sustainable management of red deer (Cervus elaphus) in Lithuania are reviewed on the basis of 57 publications and, additionally, analysis of data on numbers and hunting bag. After the extinction of the species at the beginning of the 19th century, red deer were reintroduced into the northern part of the country during World War I. Population re-establishment was further fueled after WWII by immigration from neighboring countries and local translocations. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, agricultural fields attract deer, which are important tick hosts and have been suggested to be related to the increased risk of human TBE [ 29 , 30 ]. A recent study conducted in Lithuania revealed that the deer population has been exponentially increasing in the past 20 years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, agricultural fields attract deer, which are important tick hosts and have been suggested to be related to the increased risk of human TBE [ 29 , 30 ]. A recent study conducted in Lithuania revealed that the deer population has been exponentially increasing in the past 20 years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we wrote earlier in [20], "Data on the population size and the number of hunted animals up to the 1990s were reported in the areas of forest enterprises and later in the areas of the hunting clubs. Snow-track counts with correction by the number of visually registered animals was the main method.…”
Section: Cervid Population Size and Hunting Bagmentioning
confidence: 95%
“…rely solely on official registration databases. Our previous study [53] indicated the presence of unreported ungulate roadkill in Lithuania, but their influence on the population dynamics of A. alces and C. elaphus were not discussed [19,20].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations